'Do you remember the first time?' Host plant preference in a moth is modulated by experiences during larval feeding and adult mating. (3rd March 2015) - Proffit, Magali; Khallaf, Mohammed A.; Carrasco, David; Larsson, Mattias C.; Anderson, Peter
Abstract: In insects, like in other animals, experience‐based modulation of preference, a form of phenotypic plasticity, is common in heterogeneous environments. However, the role of multiple fitness‐relevant experiences on insect preference remains largely unexplored. For the multivoltine polyphagous moth Spodoptera littoralis we investigated effects of larval and adult experiences on subsequent reproductive behaviours. We demonstrate, for the first time in male and female insects, that mating experience on a plant modulates plant preference in subsequent reproductive behaviours, whereas exposure to the plant alone or plant together with sex pheromone does not affect this preference. When including larval feeding experiences, we found that both larval rearing and adult mating experiences modulate host plant preference. These findings represent the first evidence that host plant preferences in polyphagous insects are determined by a combination of innate preferences modulated by sensory feedback triggered by multiple rewarding experiences throughout their lifetime.